Theory and Practice of Farmer Producer Organizations in Sub-National Government of Nepal: A Case of Belauri Municipality - M.Jaishi; R. Chaudhary; R. Gurung; S.R.Joshi; P.L.Chaudhary (Journal of Agricultural Extension Management, 2022)
Depending on their aims, resources, vision and institutional environment, Farmer Producer Organizations (FPOs) have diversified Rural Advisory Service (RAS) roles. FPOs particularly as major actors of RAS, specific human and social capital, knowledge, attitudes, skills and behavior have a comparative advantage over other agriculture service providers. The facts and figures related to the agriculture sector of the emerging subnational government of Nepal revealed that, there is a need for bringing sustainability in the promotion, institutionalization and capacity building of FPOs to promote economic prosperity. Against this backdrop, the paper is prepared with the support of sub-national government officials and agriculture academicians through the use of an exploratory case study method in Belauri Municipality of Kanchanpur district of far-western Nepal. The paper summarizes the status of farmer group development in sub-national government especially in restructured Nepal and how the local government's current legal framework could be utilized to streamline these opportunities. The paper concludes that the sub-national government is expected to have a comprehensive strategic plan with a solution and policy backup that could contribute to the development of FPOs in the days to come